Stress Matters: A Case Report in Occupational Therapy for Cancer-Related Cognitive Impairment - Amy Driga; Naomi Dolgoy; Julie Hunley (Scholarworks @ WMU, 2022)
Background: This case report details occupational therapy (OT) for a woman with breast cancer experiencing cancer-related cognitive impairment (CRCI), referred to OT for memory strategies. Method: Preliminary subjective and cognitive screenings were completed with further/finer assessment diarized. Results: While the cognitive aspect of CRCI is often addressed via OT, in this case, stress was the most prevalent barrier to function reported. Stress was identified as: impacting occupational engagement, CRCI presentation, interfering with return-to-work goals, and accentuated given the COVID-19 pandemic. A common cancer-specific stress screening tool appeared inadequate in identifying the impact and interplay of stress on function, necessitating a more narrative exploration around these themes. Intervention details, clinical reasoning, and outcomes are profiled in this case report. Conclusion: Current published literature showcases the multi-factorial nature of CRCI, highlighting stress as an important, though often overlooked, factor, and thus an area for OT practice growth. Developing the OT approach to functional management of CRCI involves further exploration and appreciation of the relationship between stress and function. Clinical case studies offer a foundation and serve as a first step for expanding the value of OT in approaching CRCI and stress from a functional perspective, particularly considering the stressors of the current pandemic.